THE EFFECT OF ENTREPRENEURIAL ORIENTATION AND INNOVATION CAPABILITY ON UMKM COMPETITIVENESS AND ITS IMPACT ON UMKM MARKETING PERFORMANCE IN LHOKSEUMAWE CITY - Rusydi Abubakar; T. Saifullah (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
This study examines the influence of entrepreneurial orientation and innovation capability on the competitiveness of MSMEs and their impact on the marketing performance of MSMEs in Lhokseumawe City. The sample in this study were active MSME actors and had 133 businesses. Data collected through questionnaires were analyzed using data analysis methods using Structural Equation Modeling (SEM) which was operationalized with the Analysis of Moment Structure (AMOS) tool. The results of the study indicate that entrepreneurial orientation and innovation capability have a significant effect on competitiveness and marketing performance. And competitiveness has a direct effect on marketing performance. Then in testing the indirect effect, competitiveness was found to play a role as a partial mediating variable in the relationship between entrepreneurial orientation and innovation capability on marketing performance. The results of this study are expected to be important information for the government and MSME managers in Lhokseumawe City in order to make policies for the development of micro, small and medium enterprises